2020
DOI: 10.3892/etm.2020.8597
|View full text |Cite
|
Sign up to set email alerts
|

Colonoscopic post‑polypectomy bleeding in patients on uninterruptedclopidogrel therapy: A systematic review and meta‑analysis

Abstract: Current guidelines recommend temporary cessation of clopidogrel for 7-10 days for patients on clopidogrel undergoing colonoscopy with polypectomy. However, recent prospective randomized controlled trials have advocated for uninterrupted clopidogrel, due to similar post-polypectomy bleeding (PPB) rates with and without continued clopidogrel therapy. Thus, a meta-analysis was conducted to assess the risk of PPB rate in patients on continued clopidogrel therapy. Systemically identified publications were used to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…Few meta-analyses evaluated the colonoscopic postpolypectomy bleeding in patients on antiplatelet therapy [31][32][33][34]. However, none of these assessed the risk of PPB in single APAs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Few meta-analyses evaluated the colonoscopic postpolypectomy bleeding in patients on antiplatelet therapy [31][32][33][34]. However, none of these assessed the risk of PPB in single APAs.…”
Section: Discussionmentioning
confidence: 99%
“…ASGE guidelines recommend discontinuation of thienopyridines at least 5 to 7 days before high-risk endoscopic procedure or switching to aspirin monotherapy which may be continued safely in the peri-endoscopic period [ 4 ]. Two well-conducted meta-analyses assessed the pooled relative risk ratio of colonoscopic PPB in patients who continued clopidogrel therapy; however, they both included patients on an uninterrupted single APAs therapy or DAPT [ 32 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we also evaluated the effects of anticoagulant and antiplatelet drugs on DPPB. Previous studies have shown that patients who take these drugs are more likely to suffer significant bleeding events (12,(17)(18)(19). This study showed no significant difference in antithrombotic users, probably because patients taking these drugs in our center had been asked to have a cessation for more than 5-7 days according to the guideline (20).…”
Section: Discussionmentioning
confidence: 99%
“…The groups were well matched but numbers were relatively small to examine differences in an infrequent event, and the rate of PPB in the placebo group was higher than expected when compared with other studies of patients undergoing polypectomy not previously on antiplatelet agents. A meta-analysis 76 assessing the risks of immediate and PPB associated with continued clopidogrel use at time of polypectomy included the above trial. A total of five studies were identified which included 655 patients in the 'continuing clopidogrel' group and 6620 controls with interrupted clopidogrel therapy.…”
Section: Guidelinesmentioning
confidence: 99%